BETWEEN FORMULISM AND ENUMERATION: THE NOTIONS OF SPACE AND LIMIT IN MEDIEVAL CASTILIAN-LEONESE NOTARIES - Miceli, Paola (Revista de Historia Social y de las Mentalidades, 2016)
In recent years, scholars from various  disciplines (history, geography, archaeology)  have drawn attention to the gap between  our conception of the space and that of the  medieval men. Besides this, they have also  pointed out the anachronism that involves  studying the space in Middle Ages from our  Cartesian points of view. In this context, we  propose to analyze the lists and formulae  appearing in notarial letters of donation and  sale in Castile and Leon during the 12th and  13th centuries, to investigate their role and  to establish the possible relationship between  formulae and the ways in which medieval  notaries demarcated the rights involved and  conceived the space.
Keywords: Space; Middle Age; Delimit; Formulae